Acceleration of Poor Women Capability in Increasing Income Through Self-Help Group - Prawihatmi, Chatarina Yekti (Universitas Negeri Semarang, 2018)
This study analyzedÃ‚Â the impact of the acceleration of women capabilities in creating family income through self-help group based micro credit. The analysis unit of this study are the members of UP2K-PKK (Efforts to Increase Family Income). They are poor women who run productive business.Ã‚Â The samples ofÃ‚Â this research are 177 members of the UP2K-PKK in West Semarang. The data is collected using a questionnaire that is delivered directly to the respondents along with in-depth interview. The analysis tool used is multiple linear regressions. This research tests the model that is the family income as the dependent variable and the development capability through self-help group based micro credit as the independent variable.Ã‚Â The acceleration of capability through self-help group based micro credit includes microcredit, training, partnerships, technical assistance , membership. The poor women have individual capabilities (initial endowment) including education, business experience, and membership. To know that the capability development through self-help group accelerates the development of individual capabilities, then the multiplicative variables are inserted.The results of this research show that capability development through self-help group accelerates the impact ofÃ‚Â micro credit and initial endowment in creating the family income.